Significance of teachers and education in promoting national economic development: A case study of Pakistan - Khan, Farah; Omar Fauzee, Mohd Sofian; Daud, Yaakob (Canadian Center of Science and Education, 2015)
The key objective of the present paper is to highlight the consequence of education along with the importance of teacher in education and its overall influence on the national economic development Pakistan.It is crystal clear that the role of education and teachers has become more important in improving human capital and consequently has a positive impact on the national development and prosperity.The results of this study show that teachers in all level including primary school, middle school teacher and high school teacher play a positive and statistically significant role in promoting national economic development.Therefore, these findings have some important policy implications.The government of Pakistan at both the federal and provincial levels needs to formulate appropriate and education promoting oriented policy in order to encourage education and increase quality trained teachers in the country. Consequently, it will further help to promote overall economy performance and largely mitigate poverty and improve social welfare in the country.